(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To describe the current status of antibiotic usage among surgical patients at Thai Binh provincial General Hospital in 2020. Method: Cross-sectional descriptive study reviewing 350 medical records of patients from the Departments of General Surgery and Departments of Orthopedics - Burns from May 1, 2020 to July 31, 2020. Results: Male patients accounted for 56.3%; patients over 60 years old accounted for 44.3%. Average length of hospital stay was 10.7 days. The most frequently used antibiotics were third-generation Cephalosporins (87.4%), followed by 5-nitro Imidazole (46.9%). The intravenous route was predominant (84.5%). Antibiotic combination therapy was used in 44.6% of cases, primarily combining third-generation Cephalosporins with Metronidazole. Antibiotic usage exceeding seven days was observed in 44.3% of cases. Conclusion: Antibiotic usage at the hospital remains suboptimal, with frequent prolonged and combined antibiotic therapies. Developing and implementing appropriate antibiotic stewardship program is necessary to enhance treatment effectiveness, prevent antibiotic resistance, and decrease treatment costs.